Ethyl Acetate Fraction of Gynura procumbens Mitigates Hyperglycemia, Dyslipidemia, and Tissue Damage in Streptozotocin-Induced Diabetic Rats - Mulyani, Yani; Kaniawati, Marita; Aligita, Widhya; Nugraha, Eka Rahmat (Sciences of Pharmacy, 2025)
Dyslipidemia is a lipid metabolism disorder frequently associated with diabetes mellitus and known to increase cardiovascular risk. Although Gynura procumbens has been reported to possess antidiabetic and antidyslipidemic properties, studies focusing on the specific effects of its ethyl acetate fraction remain limited. This study investigated the therapeutic potential of the ethyl acetate fraction of ethanol extract from G. procumbens in streptozotocin-induced diabetic rats, particularly its impact on blood glucose, lipid profiles, and histological changes in pancreatic and aortic tissues. Thirty rats were randomly assigned to six groups: normal control, diabetic control, glibenclamide, simvastatin, and extract-treated groups at 100 and 150 mg/kg body weight. After 28 days of treatment, the 150 mg/kg dose significantly reduced blood glucose by 61.3%, total cholesterol by 42.1%, triglycerides by 47.3%, and LDL by 55.0%, while increasing HDL by 6.3% compared to diabetic control (p < 0.05). Histological analysis demonstrated regeneration of pancreatic β-cells and improvement of vascular structure in the aorta. These findings suggest that the ethyl acetate fraction of G. procumbens may serve as a promising natural agent for managing diabetes and dyslipidemia.